Faktor-Faktor yang Memengaruhi Komitmen Generasi Z terhadap Pancasila - Primahendra, Riza; Sumbogo, Tri Adi; Lensun, Reney Aquino; Sugiyanto, Sugiyanto (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
This study intended to identify the influence of Generation Z’s perceptions on political parties and political education by mediating political leadership on the commitment to Pancasila. The study used a Partial Least Square Structural Equation Modeling (PLS-SEM) approach. The population was high school students in Jakarta. The sample was 82 students in XI grade. The results showed the perception of political parties influenced the views of political leadership (0.627). Perceptions of political parties influenced Pancasila’s commitment (0.357). The strongest influence was found to be in political education on the commitment of the Pancasila (0.722). Political education did not influence the views of political leadership (-0.009). The view of political leadership did not influence the commitment of the Pancasila (-0.194). The view of political leadership was not a factor influencing generation Z’s commitment to Pancasila. Generation Z’s commitment to Pancasila was influenced by two factors, namely political parties and political education. Political education was the highest factor influencing generation Z’s commitment to Pancasila.